Effect of particle morphology on performance of an electrostatic air–liquid interface cell exposure system for nanotoxicology studies. Issue 4 (21st April 2021) - Hsiao, Ta-Chih; Chuang, Hsiao-Chi; Lin, Jing-Chi; Cheng, Tsun-Jen; Chou, Li-Ti
Abstract: Particle morphology can affect the performance of an electrostatic precipitator air–liquid interface (ESP-ALI) cell exposure system and the resulting cell toxicity. In this study, three types of monodisperse aerosols – spherical sucrose particles, nonspherical align soot aggregates, and nanosilver aggregates/agglomerates – were selected to evaluate the collection efficiency at flow rates ranging from 0.3 to 1.5 lpm. To quantify the particle morphology, the fractal dimensions ( Df ) of the tested aerosols were characterized. The penetration of fine particles ( dp = 100–250 nm) under different operating conditions was correlated with a characteristic exponential curve using the dimensionless drift velocity ( Vc /Vavg, r ) as the scaling parameter. For nanoparticles (NPs, dp <100 nm) with different particle morphologies, the particle penetrations in the ESP-ALI were similar, but their diffusion losses were not negligible. In contrast, for fine particles, the collection efficiency of soot nanoaggregates ( Df = 2.29) was higher than that of spherical sucrose particles. This difference might be due to the simultaneous influences of the electric field-induced and flow field-induced alignment. Furthermore, based on Zhibin and Guoquan's Deutsch model, a quadratic equation was applied to fit the experimental data and to predict the performance of the ESP-ALI.